Posterior Percutaneous Pedicle Screws Fixation Versus Open Surgical Instrumented Fusion for Thoraco-Lumbar Spinal Metastases Palliative Management: A Systematic Review and Meta-analysis - Perna, Andrea; Smakaj, Amarildo; Vitiello, Raffaele; Velluto, Calogero; Proietti, Luca; Tamburrelli, Francesco Ciro; Maccauro, Giulio (Frontiers in Oncology, 2022)
Background: Surgical palliative treatment of spinal metastases (SM) could influence the quality of life (QoL) in cancer patients, since the spine represents the most common site of secondary bony localization. Traditional open posterior instrumented fusion (OPIF) and Percutaneous pedicle screw fixation (PPSF) became the main surgical treatment alternatives for SM, but in Literature there is no evidence that describes the absolute superiority of one treatment over the other. Materials and methods: This is a systematic review and meta-analysis of comparative studies on PPSF versus OPIF in patients with SM, conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The outcomes of interest were: complications, blood loss, infections, mortality, pain and also the Quality of Life (QoL). Results: There were a total of 8 studies with 448 patients included in the meta-analyses. Postoperative complications were more frequent in OPIF (odds ratio of 0.48. 95% CI, 0.27 to 0.83; p= 0.01), PPFS was associated with blood loss (odds ratio -585.70. 95% IC, -848.28 to -323.13.69; p< 0.0001) and a mean hospital stay (odds ratio -3.77. 95% IC, -5.92 to -1.61; p= 0.0006) decrease. The rate of infections was minor in PPFS (odds ratio of 0.31. 95% CI, 0.12 to 0.81; p= 0.02) whereas the occurrence of reinterventions (0.76. 95% CI, 0.25 to 2.27; p= 0.62) and the mortality rate was similar in both groups (odds ratio of 0.79. 95% CI, 0.40 to 1.58; p= 0.51). Finally, we also evaluated pre and post-operative VAS and the meta-analysis suggested that both techniques have a similar effect on pain. Discussion and Conclusion: The PPSF treatment is related with less complications, a lower rate of infections, a reduction in intraoperative blood loss and a shorter hospital stay compared to the OPIF treatment. However, further randomized clinical trials could confirm the results of this meta-analysis and provide a superior quality of scientific evidence.